The Influence of Product Quality and Service Quality on Competitiveness and Business Performance at Q Print - Alias Nabire; Lina Maretasari (GoodWill Journal of Economics, Management, and Accounting, 2025)
The printing industry plays an important role in disseminating information and communication in various forms, such as books, magazines, brochures, packaging, and advertising materials. This industry has experienced rapid development and offers a variety of printed product services, both digital and offset, according to customer needs. Product quality and service quality are fundamental factors for business performance and company competitiveness. The research was conducted at Q Print, a printing business located in Cikeas, Gunung Putri District, Bogor Regency. The purpose of this study was to determine the effect of product quality and service quality on competitiveness and business performance. The research methodology uses a quantitative approach in the form of research data measured in a numeric scale (numbers) that can be analyzed using statistical analysis. The data collection method is in the form of primary data obtained through distributing questionnaires to Q Print customers and secondary data in the form of product quality levels as supporting data. The data obtained were analyzed using descriptive statistical analysis that can describe the characteristics of respondents and research variables, multiple linear regression to determine the effect of product quality and service quality on business performance, and path analysis to test the role of competitiveness as a mediating variable. The results of this study indicate that Product Quality and Service Quality have a positive effect on Business Performance. Likewise, Product Quality and Service Quality have a significant effect on Competitiveness. While Competitiveness does not have a significant effect on Competitiveness. For indirect influence variables, both Product Quality and Service Quality on Business Performance through Competitiveness mediation do not have a significant effect.